A new green method for the quantitative analysis of enrofloxacin by Fourier-transform infrared spectroscopy - Tavares Rebouças, Camila [UNESP]; Carolina Kogawa, Ana [UNESP]; Nunes Salgado, Hérida Regina [UNESP] (Oxford University Press (OUP), 2018)
Background: A green analytical chemistry method was developed for quantification of enrofloxacin in tablets. The drug, a second-generation fluoroquinolone, was first introduced in veterinary medicine for the treatment of various bacterial species. Objective: This study proposed to develop, validate, and apply a reliable, low-cost, fast, and simple IR spectroscopy method for quantitative routine determination of enrofloxacin in tablets. Methods: The method was completely validated according to the International Conference on Harmonisation guidelines, showing accuracy, precision, selectivity, robustness, and linearity. Results: It was linear over the concentration range of 1.0–3.0 mg with correlation coefficients >0.9999 and LOD and LOQ of 0.12 and 0.36 mg, respectively. Conclusions: Now that this IR method has met performance qualifications, it can be adopted and applied for the analysis of enrofloxacin tablets for production process control. The validated method can also be utilized to quantify enrofloxacin in tablets and thus is an environmentally friendly alternative for the routine analysis of enrofloxacin in quality control. Highlights: A new green method for the quantitative analysis of enrofloxacin by Fourier-Transform Infrared spectroscopy was validated. It is a fast, clean and low-cost alternative for the evaluation of enrofloxacin tablets.